Upregulation of Peroxiredoxin-2 in Well-Differentiated Pancreatic Neuroendocrine Tumors and Its Utility as a Biomarker for Predicting the Response to Everolimus - Eui Joo Kim; Yoon Jae Kim; Hye In Lee; Seok-Hoo Jeong; Hyo Jung Nam; Jae Hee Cho (MDPI AG, 2020)
Pancreatic neuroendocrine neoplasms (pNENs) account for 2-3% of pancreatic malignancies. Peroxiredoxins (Prdxs), which are major cellular antioxidants, are involved in multiple oncogenic signaling pathways. We investigated the role of peroxiredoxin-2 in QGP-1 human pNEN cell line and patient-derived pNEN tissue. To validate the cancer stem cell-like cell characteristics of QGP-1 cells in spheroid culture, in vitro analyses and xenografting were performed. Furthermore, immunohistochemical staining was conducted to verify the overexpression of Prdx2 in pNEN tissue. Prdx2 expression was high at the mRNA and protein levels in QGP-1 cells. Prdx2 was also overexpressed in patient-derived pNEN tissue. Silencing of Prdx2 using siRNA induced overexpression and phosphorylation of ERK and AKT in QGP-1. Cell proliferation was increased by treating QGP-1 cells with siPrdx2, and the IC50 of everolimus increased suggesting resistance to everolimus. Interestingly, QGP-1 spheroid cells, which exhibited cancer stem cell-like features, exhibited lower expression of Prdx2 and mTOR. The results suggest that Prdx2 expression level and its activity may be a potential predictive biomarker for therapeutic response or resistance to everolimus in pNEN.